Renal ROCK Activation and Its Pharmacological Inhibition in Patients With Diabetes - Matoba, Keiichiro; Sekiguchi, Kensuke; Nagai, Yosuke; Takeda, Yusuke; Takahashi, Hiroshi; Yokota, Tamotsu; Utsunomiya, Kazunori; Nishimura, Rimei (Frontiers in Pharmacology, 2021)
Rho-associated coiled-coil-containing protein kinase (ROCK) is a serine/threonine kinase with essential roles in cytoskeletal functions. Substantial evidence implicates ROCK as a critical regulator in the inception and progression of diabetic nephropathy through a mechanism involving mesangial fibrosis, podocyte apoptosis, and endothelial inflammation. Despite these experimental observations, human data is lacking. Here we show that the phosphorylated form of myosin phosphatase targeting subunit 1 (MYPT1), a ROCK substrate, was increased in both the tubulointerstitial and glomerular areas in patients with histologically confirmed diabetic nephropathy. We also conducted a retrospective pilot analysis of data from patients with diabetes to assess the renoprotective effects of fasudil, an ATP-competitive ROCK inhibitor licensed in Japan for the prevention of vasospasm following subarachnoid hemorrhage. Fifteen subjects (male, n = 8; female, n = 7; age 65.7±14.7 years; body height, 161.1±12.6 cm; body weight, 57.6±13.7 kg; body mass index, 22.4±3.7 kg/m2) were enrolled to evaluate blood pressure and the renal outcome after fasudil treatment. Of note, proteinuria was significantly reduced at the end of the fasudil treatment without affecting the blood pressure or estimated glomerular filtration rate. Taken together, these findings suggest that the administration of fasudil could be associated with a better renal outcome by inhibiting the ROCK activity in patients with diabetes.